3D-Printed transmit-array antenna for broadband backhaul 5G links at V band - Matos, S.; Teixeira, J.; Costa, J. R.; Fernandes, C. A.; Nachabe, N.; Luxey, C.; Titz, D.; Gianesello, F.; Del Rio, C.; Arboleya-Arboleya, A.; Garnero, J. -P.; Vizzari, J. -F. (IEEE Antennas and Wireless Propagation Letters, 2020)
The low cost and compactness of transmit-array antennas (TAs) make them attractive for 5G backhaul links. However, the TA advantage is less obvious when considering the broadband operation requirement. Two main factors influence the bandwidth performance, namely: 1) the bandwidth of the unit cells, and 2) the number of 360° phase wrapping zones in the aperture, which are designed for a specific frequency. Herein, we overcome these limitations by using all-dielectric unit cells (inherently broadband) and by developing a general method to quantify and manage the intricate relation between antenna gain, bandwidth, and antenna height. Based on this framework we optimize, as an example, a TA design (focal distance, F=63 mm and aperture diameter D=80 mm ) to comply with typical gain specification for 5G backhaul links (>30 dBi) in the WiGiG band (from 57 to 66 GHz). The feed is a dedicated compact horn (8 ×5×22 mm3) that provides a proper illumination of the aperture. Additive manufacturing is used to simplify the manufacturing process of the antenna. A very good agreement between simulations and experimental results is obtained, achieving good aperture efficiency for this type of antenna (42%), which rivals with existing solutions based on more expensive manufacturing techniques.